Intravenous leiomyomatosis is inclined to a solid entity different from uterine leiomyoma based on RNA‐seq analysis with RT‐qPCR validation - Wenze Wang; Yanfeng Wang; Fei Chen; Ming Zhang; Rujing Jia; Xingrong Liu; Chaoji Zhang; Jiang Shao; Ninghai Cheng; Guotao Ma; Zhaohui Zhu; Qi Miao; et al. (Cancer Medicine)
Abstract Introduction Intravenous leiomyomatosis (IVL) is currently regarded as a special variant of the common uterine leiomyoma (LM). Though IVL shows a similar histological morphology to LM, IVL is characterized by unique intravenous growth patterns and low‐grade malignant potential, which are quite different from LM. There are currently few studies underlying the molecular alterations of IVL, though this information is important for understanding the pathogenesis of the disease, and for identifying potential biomarkers. Method We carried out a high‐throughput whole transcriptome sequencing of tumor and normal tissue samples from five IVL patients and five LM patients and compared the differentially expressed genes (DEGs) between IVL and leiomyoma. We performed multiple different enrichment and target analyses, and the expression of selected DEGs was validated using RT‐qPCR in formalin‐fixed samples. Results Our study identified substantial different genes and pathways between IVL and LM, and functional enrichment analyses found several important pathways, such as angiogenesis and antiapoptosis pathways, as well as important related genes, including SH2D2A, VASH2, ADAM8, GATA2, TNF, and the lncRNA GATA6‐AS1, as being significantly different between IVL and LM (P = .0024, P = .0195, P = .0212, P = .0435, P = .0401, and P = .0246, respectively). CXCL8, LIF, CDKN2A, BCL2A1, COL2A1, IGF1, and HMGA2 were also differently expressed between IVL and LM groups, but showed no statistical difference (P = .2409, P = .1773, P = .0596, P = .2737, P = .1553, P = .1045, and P = .1847, respectively) due to the large differences among individuals. Furthermore, RT‐qPCR results for five selected DEGs in IVL tissues and adjacent nontumor tissues were mainly consistent with our sequencing results. Conclusion Our results indicated that IVL may be a solid entity that is unique and different from LM, proving consistent with previous studies. Furthermore, we identified DEGs, particularly within angiogenesis and antiapoptosis pathway‐related genes that may play crucial roles in the development and pathogenesis of IVL and may be potential specific biomarkers.